2015
DOI: 10.1093/trstmh/trv079
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical and laboratory associations of severity in a Sri Lankan cohort of patients with serologically confirmed leptospirosis: a prospective study

Abstract: Severity associations were demonstrated with both clinical and laboratory parameters. There is a need for novel biomarkers for prediction of severity in leptospirosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The criteria of definingdisease complications; myocarditis, acute respiratory distress syndrome, pulmonary haemorrhage, acute liver failure, acute renal injury, shock and multi-organ dysfunction syndrome mentioned in the Table 2 were adopted from Rajapakse etal. 2015 [ 37 ]…”
Section: Resultsmentioning
confidence: 99%
“…The criteria of definingdisease complications; myocarditis, acute respiratory distress syndrome, pulmonary haemorrhage, acute liver failure, acute renal injury, shock and multi-organ dysfunction syndrome mentioned in the Table 2 were adopted from Rajapakse etal. 2015 [ 37 ]…”
Section: Resultsmentioning
confidence: 99%
“…39,40 Some studies found hypotension, haemorrhage, cardiovascular collapse, male gender, old age, alcohol intake, hight ALT, high bilirubin, metabolic acidosis and need for ventilatory support to be predictors of poor prognosis. 3,14,31,41 In the present study, hepato-renal involvement, presence of underlying cirrhosis and need for artificial ventilation were predictors of mortality. Similar results have been reported by Somasundaram et al 15 where all the deaths were due to cirrhosis and hepato-renal involvement.…”
Section: Discussionmentioning
confidence: 48%
“…Previous studies about the clinical factors associated with severe leptospirosis have shown signs and symptoms like hemorrhage [ 33 ], pulmonary signs and symptoms (abnormal lung sounds, dyspnea) [ 33 ], hypotension, oliguria, jaundice [ 52 , 53 ], and hyperkalemia [ 33 ]. Laboratory testing as packed cell volume (PCV: 29.8%), hyponatremia (<131 mEq/L), and highest alanine transaminase (ALT: 70 IU/L) were found to be independently associated with severe disease [ 52 , 54 ]. We found rash, dyspnea, tachycardia, and jaundice associated with severe leptospirosis.…”
Section: Discussionmentioning
confidence: 99%